Fas and Fas-Ligand in Eutopic and Ectopic Endometrium of Women With Endometriosis: The Possible Immune Privilege of Ectopic Endometrium. (January 2016) - Sbracia, Marco; Valeri, Claudia; Antonini, Gabriele; Biagiotti, Giulio; Pacchiarotti, Alessandro; Pacchiarotti, Arianna
The Fas/Fas-Ligand system is an important mediator of apoptosis. We analyzed their expression in tissue specimens obtained from 33 women with severe endometriosis and 18 women without endometriosis. Immunostaining for Fas-Ligand in the eutopic endometrium was stronger in the epithelial cells of secretory phase, while the epithelial cells of endometriotic lesions showed a significantly stronger staining for Fas-Ligand independently from the menstrual phase ( P < 0.01). Immunostaining for Fas in the eutopic endometrium showed a reduced staining during the proliferative phase, whereas it was strong in the secretory phase. The epithelial cells of the ectopic endometrium showed a reduced staining for Fas independently from the menstrual phase with respect to the eutopic tissue ( P < 0.01). The reduced expression of Fas in the ectopic endometrium with the contemporary higher expression of Fas-Ligand in the corresponding cells suggests a possible immune privilege of this tissue.